A small open economy in the great depression: The case of Switzerland - Peter Rosenkranz; Tobias Straumann; Ulrich Woitek (University of Zurich, Department of Economics, 2014)
In historical accounts of the world economic crisis of the 1930s, Switzerland is known for its staunch defense of the gold standard and the rise of corporatist policies. Yet, so far, the literature has not discussed the implications of these two features. This paper tries to show how the combination of hard-currency policy and nominal rigidities introduced by corporatist policies proved to be fatal for growth. Estimating a New Keynesian small open economy model for the period 1926-1938, we show that the decision to participate in the Gold Bloc after 1933 at an overvalued currency can be identified as the main reason for the unusual long lasting recession and that price rigidities from 1931 to 1936 significantly slowed down the adjustment process.
Keywords: E12; E32; N14; 330; Great Depression; Switzerland; New Keynesian Business Cycle Model